Suicide Screening Among Youth at First Court Contact. Issue 2 (3rd April 2022) - Kemp, Kathleen; Yurasek, Ali M.; Poindexter, Brittney; Webb, Margaret; Tolou-Shams, Marina
Abstract: Youth involved in the juvenile justice system are at elevated risk for suicide and co-occurring mental health symptoms. This study aims to examine the suicide risk and treatment needs of court-involved, non-incarcerated (CINI) youth, and to understand the acceptability and effectiveness of implementing a mental health screening procedure at time of first court contact. By embedding a forensic mental health screening tool into the intake process of a family court diversionary program, a total of 891 youth (aged 12–18) were assessed using the Massachusetts Youth Screening Instrument-2 (MAYSI-2). Analysis of screening responses revealed 12.5% of youth indicated risk for suicide with risk levels differentiated by youth sex, race and ethnicity. Suicide ideation was also significantly associated with flagging, an indication of clinical risk, on all other scales of the MAYSI-2, as well as subsequent referrals to treatment. Screening for suicide at first point of court contact within an existing diversionary program may serve as a critical and effective point of intervention for youth in need.